Genome-wide expression analysis of endometrium before and after endometrioma surgery - Celik, Onder; Celik, Nilufer; Zan, Ertan; Dalkilic, Semih; Saglam, Aylin; Yurci, Arzu; Sahin, Mefkure Eraslan (Elsevier, 2020)
Objective: This study was planned to investigate possible alteration in the number of differentially expressed genes (DEGs) in eutopic endometrium before and after laparoscopic removal of the ovarian endometrioma. Study design: Six infertile women with ovarian endometrioma who underwent laparoscopic endometrioma cystectomy and six fertile control subjects who underwent tubal sterilization were included the study. Endometrial samples were collected before and 3 months after surgery throughout the mid-luteal phase. Genome-wide expression profiling was performed with Illumina Human HT-12V4 microchip, a high density silica bead-based microarray which utilizing more than 47.000 probs. Illumina microsequence system was used to assess detection of p value for each probe in every sample. Probes revealing significant assessment (p < .05) were selected for comparative analysis. Results: We have detected 1478 DEGs in the comparison between endometrium of women with endometrioma and fertile controls.118 out of 1478 genes (7.9 %) were significantly increased or decreased more than 1.5-fold in their expression. When the preoperative values of the control and patient groups are compared the number of DEGs was 243 (7.5 %). In 9 out of 243 genes, the fold change was found to be 1.5 and more (3.7 %). Comparison of the number of DEGs after endometrioma surgery and tubal ligation revealed that expression patterns of 1036 genes (33.7 %) were changed in endometrioma group. In 105 out of 1036 genes, the fold change was found to be 1.5 and above (10 %). A comparison using 2706 probes revealed changes in the expression patterns of 106 different genes (3.9 %) after endometrioma resection. In 4 out of 106 genes, the fold change was found to be 1.5 and above (3.7 %). The comparison using 6035 probes revealed changes in the expression patterns of 93 genes (1.5 %) after tubal ligation. None of the 93 genes had a fold change of 1.5 or higher. The number of DEGs in endometrioma groups after surgery was approximately 3-fold higher than control group. Conclusions: Endometrium of women with endometrioma displayed abnormal expression of genes associated with implantation, immunological, endocrine and neuracrine functions. Positive alteration of the expression pattern of DEGs and signal transduction pathways following endometrioma surgery can improve the receptive capacity and implantation rates of eutopic endometrium. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Endometrioma surgery; Eutopic endometrium; Receptivity; Genome-wide expression analysis; Illumina